The morphology of CLL revisited: the clinical significance of prolymphocytes and correlations with prognostic/molecular markers in the LRF CLL4 trial. (6th May 2016) - Oscier, David; Else, Monica; Matutes, Estella; Morilla, Ricardo; Strefford, Jonathan C.; Catovsky, Daniel
Summary: Historically, an increase in the percentage and number of circulating prolymphocytes in chronic lymphocytic leukaemia (CLL) has been associated with strong expression of surface immunoglobulin, trisomy 12 and a poor outcome. This study re‐examines the biological and clinical significance of increased peripheral blood prolymphocytes in 508 patients at entry into the randomized UK Leukaemia Research Fund CLL4 trial. It also investigates the associations between increased prolymphocytes and a comprehensive array of biomarkers. 270 patients (53%) had <5% prolymphocytes, 167 (33%) had 5–9%, 60 (12%) had 10–14% and 11 (2%) had ≥15% prolymphocytes. We show that a higher proportion of prolymphocytes (≥10%) was independently associated with NOTCH1 mutations ( P  = 0·006), absence of 13q deletion ( P  = 0·001), high CD38 expression ( P  = 0·02) and unmutated IGHV genes ( P  = 0·01). Deaths due to Richter syndrome were significantly more common amongst patients who had ≥10% vs <10% prolymphocytes (13% vs 2%) respectively ( P  < 0·0001). ≥10% prolymphocytes was also associated with a shorter progression‐free survival (Hazard ratio [HR] 1·50 [95% confidence interval [CI]: 1·16–1·93], P  = 0·002) and overall survival (HR 1·99 [95% CI: 1·53–2·59], P  < 0·0001). Our data support the routine examination of blood films in CLL and suggest that a finding of an increased proportion of prolymphocytes may be a trigger for further evaluation of clinical and laboratory features of progressive disease.